2008
DOI: 10.1108/07363760810902495
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity, expertise and involvement: key consumer segmentation factors

Abstract: Purpose -It is generally accepted that the launch of a new product is critical to its success. Key to this is that manufacturers understand the market segment which is targeted for the launch. However, recent research and criticism suggest that modern segmentation strategies, aligning products with lifecycle typologies do not work. It is no longer possible to align consumers and products into neat and stable lifecycle segments. It is suggested that more importance should be attached to products having a famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The objective of this study was to establish the current reliability and validity of using the reduced item scales of AIS and Expertise suggested by Taylor-West et al (2008).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The objective of this study was to establish the current reliability and validity of using the reduced item scales of AIS and Expertise suggested by Taylor-West et al (2008).…”
Section: Methodsmentioning
confidence: 99%
“…More recent research by Taylor-West et al (2008) suggested that this could be reduced even further to two items -exploratory factor analysis indicating that a two item scale explained 77.89% of the variance. This may appear to be a quest for reduced item scales, but they do have significant benefits.…”
Section: Literature Reviewmentioning
confidence: 98%
See 3 more Smart Citations